2015
DOI: 10.18488/journal.87/2015.2.1/87.1.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Integrated Nutrient Management Practices for Sustainable Crop Productivity, Nutrient Uptake and Soil Nutrient Status in Maize Based Cropping Systems

Abstract: Over applications of inorganic fertilizers lead nutrient imbalances, inefficiency and environmental contamination while insufficient application of nutrients causes soil fertility depletion. This problem drives Journal of Nutrients 2015 Vol. 3, No. 2, pp. 21-26 ISSN(e): 2410 Contribution/ OriginalityThis study contributes in the existing literature to give recent information on the importance of judicious use of integrated nutrient management that improve sustainable productivity of maize based cropping syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The use of chemical fertilizers is one of the ways to restore depleted nutrients. However, the higher cost of chemical fertilizers coupled with their low affordability by small farmers is the biggest obstacle for their use [2]. Additionally, the improper and imbalanced use of chemical fertilizers deteriorated soil health by producing serious effects on soil microorganisms, soil enzymatic activities, the atmosphere, and groundwater quality, causing health hazards and climate change [3].…”
Section: Introductionmentioning
confidence: 99%
“…The use of chemical fertilizers is one of the ways to restore depleted nutrients. However, the higher cost of chemical fertilizers coupled with their low affordability by small farmers is the biggest obstacle for their use [2]. Additionally, the improper and imbalanced use of chemical fertilizers deteriorated soil health by producing serious effects on soil microorganisms, soil enzymatic activities, the atmosphere, and groundwater quality, causing health hazards and climate change [3].…”
Section: Introductionmentioning
confidence: 99%
“…Research has suggested that integrated nutrient management strategies involving chemical fertilizers and bio-fertilizers enhance the sustainability of crop production. Integrated plant nutrient managet (INM) is the combined use of mineral fertilizers with organic resources such as cattle manures, crop residues, urban/rural wastes, composts, green manures and biofertilizers (Kemal and Abera, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…High and stable yield could be attained through reasonable and balanced fertilization of organic and inorganic fertilizers [36]. Several studies showed INM significantly improved yield and yield traits of maize [37]. e combined use of poultry manure and chemical fertilizer was more effective in increasing nutrient availability and maize performance than the sole application of any of the fertilizers [38].…”
Section: Effect Of Integrated Nutrient Management On Maize Productionmentioning
confidence: 99%